(untitled) (Tanzania Medical Journal, 2007)
Background: Thromboembolic and anticoagulant related bleeding complications are the main causes of morbidity and mortality in patients with mechanical heart valves. A review of articles published since 1979 indicates that thromboembolic and bleeding complications account for about 75% of valve-related complications in patients with mechanical heart valves (2). However, the magnitude of these complications in Tanzania has not been established. Objective: This study was conducted to determine the incidence of thromboembolic and bleeding complications among patients with mechanical heart valves operated from 1990 to 2003 attending the Muhimbili National Hospital. Study design: This was a retrospective cohort study conducted at the cardiac, anticoagulation clinics and medical records section. Study settings: The study was conducted in Dar es Salaam at Muhimbili National Hospital in either the cardiac or anticoagulant clinics. Measure of outcome: The incidence rate of complications was reported as the number of complications per patient year of observation. Survival curves were obtained using the method of Kaplan and Meier to determine the freedom (survival) rate from either thromboembolic or bleeding complications. The time taken to develop a first complication since valve replacement was used for analysis. Subjects: All patients with mechanical heart valves who were operated from 1990 to 2003 attending the Muhimbili National Hospital Methodology: Determination of complications involved tracing complications recorded in the file for all patients. This also included tracing their operational (surgical) notes to obtain their baseline demographical and surgical information .Additional collaborative information, by interview, was added for patients who were still attending the clinics Results: Among the 232 study patients, 59 (25.4%) suffered a total of 83 thromboembolic episodes. The linearized incidence of minor (grade I and II) episodes was 5.5% person-years and 3.5 % person-years for major (grade III) episodes. The study also indicated that 87 (37.5%) patients suffered a total of 132 bleeding events. The linearized incidence rate of minor bleedings was 11.4% person-years while that of major bleeding was 2.9 % person-years. Conclusion and recommendation: It was concluded that the incidence of both thromboembolic and bleeding complications was high among study patients. It was recommended to conduct further studies that will focus on the factors contributing to this high incidence Tanzania Medical Journal Vol. 22 (1) 2007: pp. 12-16